Detrimental effects of simulated microgravity on mast cell homeostasis and function - Kim, Minjin; Jang, Gyeongin; Kim, Kyu-Sung; Shin, Jinwook (Frontiers in Immunology, 2022)
Exposure to microgravity causes significant alterations in astronauts’ immune systems during spaceflight; however, it is unknown whether microgravity affects mast cell homeostasis and activation. Here we show that microgravity negatively regulates the survival and effector function of mast cells. Murine bone marrow-derived mast cells (BMMCs) were cultured with IL-3 in a rotary cell culture system (RCCS) that generates a simulated microgravity (SMG) environment. BMMCs exposed to SMG showed enhanced apoptosis along with the downregulation of Bcl-2, and reduced proliferation compared to Earth’s gravity (1G) controls. The reduction in survival and proliferation caused by SMG exposure was recovered by stem cell factor. In addition, SMG impaired mast cell degranulation and cytokine secretion. BMMCs pre-exposed to SMG showed decreased release of -hexosaminidase, interleukin-6 (IL-6), and tumor necrosis factor- (TNF-) upon stimulation with phorbol 12-myristate-13-acetate (PMA) plus calcium ionophore ionomycin, which correlated with decreased calcium influx. These findings provide new insights into microgravity-mediated alterations of mast cell phenotypes, contributing to the understanding of immune system dysfunction for further space medicine research.